1999
DOI: 10.1046/j.1365-2044.1999.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose bupivacaine: a comparison of hypobaric and near isobaric solutions for arthroscopic surgery of the knee

Abstract: SummaryThe results of studies on the effect of volume, concentration or total dose of local anaesthetic on the spread of spinal anaesthesia are inconclusive. Most support the assumption that the total dosage is more important than the volume. We compared low-dose bupivacaine (6 mg) in 0.5% and 0.18% solutions as sole anaesthetic to achieve predominantly unilateral spinal anaesthesia for knee arthroscopy. Sixty patients were randomly allocated to two groups to receive either 1.2 ml 0.5% bupivacaine (6 mg) (n ¼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 20 publications
5
22
0
3
Order By: Relevance
“…Unilateral spinal anesthesia minimizes the hemodynamic effects of the local anesthetic drug (24)(25)(26). In our study, in group1, there were no hypotension and low HR and none of the patients required fluid load and vasopressor agent but in group 2, 3 patients required fluid load and vasopressor agent due to hypotension and low heart rate.…”
Section: Discussionmentioning
confidence: 48%
“…Unilateral spinal anesthesia minimizes the hemodynamic effects of the local anesthetic drug (24)(25)(26). In our study, in group1, there were no hypotension and low HR and none of the patients required fluid load and vasopressor agent but in group 2, 3 patients required fluid load and vasopressor agent due to hypotension and low heart rate.…”
Section: Discussionmentioning
confidence: 48%
“…As the hemodynamic stability provided by unilateral spinal anesthesia does not necessitate over-hydration, another advantage of unilateral anesthesia is that unilateral sacral parasympathetic plexus blockage does not completely disturb the detrusor muscle function. In the present study, two patients in group Hypo and 7 patients in group Hyper complained of urinary retention and were catheterized once, micturating spontaneously 6,10 .…”
Section: Discussionmentioning
confidence: 72%
“…Kuusinami et al 10 and Casati et al 23 reported that the incidence of hypotension was lower with unilateral spinal anesthesia than with conventional spinal anesthesia. Pre-hydration is one of the factors that minimize hypotension following spinal anesthesia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A dose de 7,5 mg bupivacaína hipobárica a 0,15% associada a fentanil tem um período de recuperação de 2,94 horas 9 , similar aos 2,96 obtidos com 6,1 mg de bupivacaína a 0,18% 26 . Diminuição da dose de bupivacaína a 0,15% hipobárica para 5 mg reduz o tempo de recuperação para 2,32 horas, representando diminuição de 20% 10 .…”
Section: Discussionunclassified